Morpho-agronomy performance, seed nutrition content, and Aphis craccivora resistance of cowpea (Vigna unguiculata) genotypes (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sas MGA, Wahyu Y, Syukur M, Hidayat P. 2021. Morpho-agronomy performance, seed nutrition content, and Aphis craccivora resistance of cowpea (Vigna unguiculata) genotypes. Biodiversitas 22: 4320-4326. Cowpea (Vigna unguiculata subsp. unguiculata) is an agricultural commodity that can be a source of vegetable protein and replace the need for soy as a food ingredient. The wide adaptability under sub-optimum conditions placed cowpeas as the choice to be developed. This study aimed to evaluate the cowpea genotype’s agronomic performance and resistance to Aphis craccivora to be proposed as superior genotypes. Observations were made on the morpho-agronomic characters, including the color of the young pods and dry seeds, the number of pods, the productivity of fresh pods and dried seeds, and the nutrition content. The resistance to Aphis craccivora was evaluated using a no-choice test whole plant for the resistance and tolerance evaluation. This study showed that the productivity of young pods (4.86-15.13 tons ha-1), dry seed productivity (0.83-2.71 tons ha-1). The protein content differed significantly among the 20 genotypes ranging from 19.24% to 24.45%. Aphid infestation significantly inhibited plant growth compared with non-infested plants. Infestation of Aphis craccivora decreased the dry weight of the plant by about 20% to 70%. Based on the aphid population, the 20 genotypes were classified into medium-high to very high aphid damage intensity.
Keywords: agronomy; aphids; cowpeas; characterization; infestation